Testing for intertemporal nonseparability - Ian Crawford; Matthew Polisson (Institute for Fiscal Studies (IFS), 2013)
This paper presents a nonparametric analysis of a common class of intertemporal models of consumer choice that relax consumption independence. Within this class and in the absence of any functional form restrictions on instantaneous preferences, we compare the revealed preference conditions for rational habit formation and rational anticipation. We show that these models are nonparametrically equivalent in the presence of finite date sets composed of prices, interest rates, and consumption choices.
Keywords: D11; D12; D91; 330; anticipation; habits; revealed preference; time separability